Becoming a Circular Ecosystem : Altering Nested Identities, Positions, Capabilities, and Boundaries in Waste-Management Organizations - Huikkola, Tuomas; Kohtamäki, Marko; Rabetino, Rodrigo (SAGE, 2025)
This study aims to understand how organizations within modern waste-management ecosystems pursue strategic change from a linear economy to a circular economy logic. This paper draws on complementary firm theory perspectives to examine the interplay of management practices that enable organizations in waste-management ecosystems to become circular by altering their identities, capabilities, power positions, and boundaries. Based on an in-depth study of organizations in one waste-management ecosystem in Finland, this study identifies several management practices associated with identity and capability-building, repositioning, and boundary decision-making that facilitate the green transition. This study enables managers to benchmark systemic transitions in established, conservative, and regulated organizations and ecosystems and highlights that the implications of strategic practices extend beyond focal companies.
Keywords: theory of a firm; boundaries; ecosystem; sustainability; circular economy; business models; fi=Strateginen johtaminen|en=Strategic Management|